2020
DOI: 10.1007/s10508-020-01766-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender Nonconformity of Bisexual Men and Women

Abstract: The degree to which bisexual-identified individuals are distinct from either heterosexual or homosexual individuals in their sexual orientation is an ongoing debate. We examined potential differences between these groups with respect to a strong correlate of sexual orientation, gender nonconformity (femininity in males, masculinity in females). Across pooled data, we compared self-reports of childhood gender nonconformity (n = 919) and adulthood gender nonconformity (n = 1265), and observer ratings of adulthoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We decided against including bisexual individuals in the study for several reasons. While there is some evidence to suggest a level of gender nonconformity also in bisexual individuals, they are not as gender nonconforming: Some reports suggest that their level of gender nonconformity is intermediate between heterosexual and homosexual individuals (e.g., Rieger et al, 2020 ). Moreover, it is likely that mental health risk among bisexuals might be unique to bisexual people, and while it may also be related to their gender nonconformity, this relationship is probably less strong than in exclusively gay/lesbian people.…”
Section: Introductionmentioning
confidence: 99%
“…We decided against including bisexual individuals in the study for several reasons. While there is some evidence to suggest a level of gender nonconformity also in bisexual individuals, they are not as gender nonconforming: Some reports suggest that their level of gender nonconformity is intermediate between heterosexual and homosexual individuals (e.g., Rieger et al, 2020 ). Moreover, it is likely that mental health risk among bisexuals might be unique to bisexual people, and while it may also be related to their gender nonconformity, this relationship is probably less strong than in exclusively gay/lesbian people.…”
Section: Introductionmentioning
confidence: 99%
“…A final point concerns bisexual women, who were intermediate between heterosexual and homosexual women in their sexual arousal and masculinity-femininity, but were significantly more feminine in their 2D:4D. One hypothesis is that due to intermediate dosages of genetic or prenatal hormonal influences, bisexual individuals, who could be considered to have sexual orientations between heterosexual and homosexual, also fall intermediate with respect to correlates of sexual orientation (Rieger et al, 2020). Thus, regarding bisexual women's 2D:4D, we assumed that they could also be intermediate between heterosexual and homosexual women on this measure.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence of comorbidity not only among mental conditions, but also between mental and physical con ditions, as shown by studies pointing to transdiagnostic asso ciations across a wide range of physical and mental disorders 1,5 . These findings suggest that there may be another factor that ac counts for the individuals' propensity to develop mental as well as physical conditions, that we termed the "d" (for disease) factor 6 .…”
Section: Childhood Gender Non-conformity Sexual Orientation and Menta...mentioning
confidence: 99%
“…Prior research on this topic has focused primarily on non‐probability‐based samples of young people and sexual or gender identity minority groups, documenting strong links between childhood gender non‐conformity and both non‐heterosexuality and non‐cisgender identity 3‐5 . Same‐sex oriented individuals considerably more often report childhood gender non‐conformity than heterosexual peers, and it has been suggested that childhood gender non‐conformity might, at least in part, explain the excess mental morbidity observed among sexual minorities 6,7 .…”
mentioning
confidence: 99%